All-solid-state sodium storage battery, battery pack including said storage battery, and electrical device equipped with said storage battery
Patent Information
- Application Number
- JP2020166580
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-30
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2040-09-30
AI Technical Summary
【0047】 本発明の請求項1の全固体ナトリウム蓄電池によれば、有機固体電解質が、電極合材と無機固体電解質との間に介在して構成されたため、優れた充放電サイクル特性を発揮し、かつ過充電でシャットダウンすることができる蓄電池を実現することができる。また、該有機固体電解質がポリエチレングリコール又はポリエチレンオキシドを含むため、固体電解質としての機能と、電極合材と無機固体電解質を結合させる粘着剤としての機能を実現することができ、前記有機固体電解質が、さらにナトリウム塩を含み、前記有機固体電解質の重量を1とした場合、前記ナトリウム塩が0.1~1.5の範囲内であるため、電極と固体電解質との接着作用でイオン伝導性が保持でき、電池の充放電サイクル特性が得られる。
Smart Images

Figure 0007640038000003 
Figure 0007640038000004 
Figure 0007640038000005
Abstract
Description
[Technical field]
[0001] The present invention relates to an all-solid-state sodium storage battery, a battery pack including the storage battery, and an electrical device including the storage battery. [Background technology]
[0002] The fields of use for storage batteries (secondary batteries) with high energy density have expanded from power sources for portable devices such as smartphones and tablet terminals to electric vehicles, power storage, etc. In particular, automobile manufacturers are actively developing and commercializing clean automobiles (electric vehicles, plug-in hybrid vehicles, etc.) in order to comply with environmental regulations aimed at reducing automobile exhaust gases and carbon dioxide (CO2) worldwide.
[0003] In addition, renewable energy sources such as wind and solar power require large-scale battery storage systems because the amount of power generated fluctuates greatly due to environmental influences. Recently, the cost of generating electricity from renewable energy sources has fallen to less than half that of coal-fired power generation, and their share of power generation is expanding. In view of their future widespread use, there is a need to increase battery production.
[0004] Storage batteries are essential for energy conservation, the introduction of new energy sources, and clean automobiles, and are positioned as important key devices from the perspective of economic growth in each country.
[0005] Current storage batteries, including lithium-ion batteries, have driven the electronics and automotive industries, but insufficient temperature characteristics and safety assurance have delayed their widespread use depending on the battery's application. Therefore, it is desirable to develop new batteries that are suitable for the application while simultaneously improving battery performance and ensuring safety. In addition, for rare metals and resources that are unevenly produced, risk management is important in consideration of fluctuations in market prices and the risk of becoming difficult to obtain. Although the development of rare metal recycling technology has progressed from various angles, there is a demand for the development of batteries made of materials that are inexpensive, easy to obtain, and not unevenly produced (see Non-Patent Documents 1 and 2).
[0006] Currently, development of sodium-ion batteries and all-solid-state batteries is progressing as battery systems that can solve these issues.
[0007] Sodium is abundant in seawater and is the sixth most abundant element in the earth's crust. It is cheap, easy to obtain, and not unevenly distributed like lithium. This reduces the risk of procuring resources, and is expected to reduce the cost of batteries.
[0008] It is an extremely attractive element in light of the recent trend toward rare metal-free batteries, but compared to lithium, its redox potential is about 0.3 V higher, its ion volume is more than twice as large, and its atomic weight is about 3.3 times larger. Simply replacing the ion species in conventional lithium-ion batteries with sodium ions makes it difficult to obtain sufficient electrical capacity and cycle characteristics.
[0009] Other battery systems that use sodium include sodium-sulfur batteries and sodium-metal chloride batteries. Sodium-sulfur batteries are constructed using sodium-containing aluminum oxide, such as β-alumina or β''-alumina, as the solid electrolyte, sodium as the negative electrode active material, and sulfur as the positive electrode active material.
[0010] In sodium-metal chloride batteries, the solid electrolyte and the negative electrode active material are the same, but metal chlorides such as NaAlCl4, NiCl2, FeCl2, CoCl2, and CrCl2 are used as the positive electrode active material.
[0011] Although sodium-sulfur batteries and sodium-metal chloride batteries do not require an electrolyte solvent, unlike lithium-ion batteries and sodium-ion batteries, they do not operate at room temperature. For this reason, the temperature of the battery is maintained at 250 to 350°C using an external heat source, etc., and the negative and positive active materials are kept in a molten state to improve the ionic conductivity of the solid electrolyte.
[0012] On the other hand, an all-solid-state battery is a battery system that uses a solid electrolyte. Because this solid electrolyte is responsible for ionic conduction between the positive and negative electrodes, all-solid-state batteries can be produced without using the organic solvents that were previously required for sodium-ion batteries (sodium storage batteries that use electrolytes). For example, sodium-ion batteries have traditionally used sodium hexafluorophosphate (NaPF6) salt as the electrolyte, but sodium ions (Na + ), as well as hexafluorophosphate ion (PF6 - ) also moves, making it difficult to make the transport number of the sodium ion 1.
[0013] However, inorganic solid electrolytes do not undergo concentration polarization, and the transport number of sodium ions is nearly 1. By selecting an electrolyte with an appropriate potential window, it is possible to suppress side reactions such as the dissolution reaction of active materials, gas generation due to electrolysis, and precipitation of electrolyte decomposition products in all-solid-state batteries. In addition, all-solid-state batteries are less susceptible to gas or liquid ignition and liquid leakage, and are expected to become storage batteries with excellent safety and reliability.
[0014] Like conventional batteries, all-solid-state sodium batteries are composed of a positive electrode, a negative electrode, and an electrolyte, but the electrolyte must be solid and have sodium ion conductivity.
[0015] The positive and negative electrodes are composed of an active material capable of absorbing or alloying sodium ions during charging and discharging, and a solid electrolyte. For example, materials such as TiS2 (see, for example, Non-Patent Document 3), NaMO2 (hereinafter, M is Co, Ni, Mn, or Fe) (see, for example, Non-Patent Documents 4 to 6), Na2MnO3-NaMO2 (see, for example, Patent Document 1), and NaMP2O7 (see, for example, Patent Document 2) are known as active materials used in the positive electrode. Hard carbon (see, for example, Patent Document 3), soft carbon (see, for example, Patent Document 4), simple substances or compounds such as tin and antimony (see, for example, Patent Documents 5 and 6), and sodium metal are known as active materials used in the negative electrode.
[0016] Through vigorous research and development, various solid electrolytes exhibiting high ionic conductivity have been found (see, for example, Patent Documents 7 to 10). Many of them are amorphous or crystalline composed of sodium salts and inorganic derivatives. However, these are powdered or sheet-like materials, and many of them have properties that are highly reactive with water, so conventional battery production methods cannot be applied as they are. Specifically, in an all-solid-state sodium storage battery, unlike a liquid-type sodium ion battery, it is difficult to permeate the electrolyte into the active material layer of the electrode to construct an ionic conduction path. For this reason, it is necessary to include a solid electrolyte in the active material layer to increase the ionic conductivity between the solid electrolyte and the solid particles of the active material.
[0017] For example, Patent Document 11, Patent Document 12, and Non-Patent Document 7 propose preparing an electrode mixture precursor (active material layer precursor) containing an active material precursor powder and a solid electrolyte powder, and then firing the electrode mixture precursor (active material layer) consisting of an active material and a solid electrolyte, or an all-solid-state sodium storage battery using the electrode mixture precursor. For example, Na2FeP2O7 crystallized glass is used as the active material precursor. Glass and crystallized glass are crystallized by firing (heat treatment), and softening and flow occur during this process. Therefore, the active material precursor can be integrated with the solid electrolyte powder by firing alone, without applying pressure.
[0018] According to Patent Document 11, Patent Document 12, and Non-Patent Document 7, the electrode mixture precursor is applied to one surface of a solid electrolyte layer, and then fired at 400° C. or higher to form an electrode mixture on one surface of the solid electrolyte layer.
[0019] However, since solid electrolytes do not have electronic conductivity, it is difficult to ensure both electronic and ionic conductivity of the electrode. In response to this, it is possible to add a conductive additive, but if the content of the conductive additive is too high, the amount of active material per unit mass of the electrode mixture decreases, and the charge / discharge capacity tends to decrease. In addition, the ion conduction path is cut off by the inhibition of sintering, and there is concern (suggestion) that the charge / discharge capacity and discharge voltage will decrease. [Prior art documents] [Patent documents]
[0020] [Patent Document 1] JP 2014-229452 A [Patent Document 2] JP 2018-32536 A [Patent Document 3] International Publication No. 2010 / 109889 [Patent Document 4] JP 2013-171798 A [Patent Document 5] International Publication No. 2013 / 065787 [Patent Document 6] JP 2015-28922 A [Patent Document 7] JP 2010-15782 A [Patent Document 8] JP 2017-37769 A [Patent Document 9] JP 2019-57495 A [Patent Document 10] JP 2019-57496 A [Patent Document 11] JP 2018-18578 A [Patent Document 12] JP 2016-42453 A [Non-patent literature]
[0021] [Non-Patent Document 1] Takashi Mukai: Automotive Technology, 5(4), 19-24(2018) [Non-Patent Document 2] Takashi Mukai: "Lithium-ion batteries - developments to improve performance and trends in the automotive LIB industry", Part 1, Chapter 6, Science & Technology, pp.91-94(2019) [Non-Patent Document 3] GH Newman,LPKlemann:J.Electrochem.Soc.127,2097-2099(1980) [Non-Patent Document 4] J.-J. Braconnier, C. Delmas, C. Fouassier, P. Hagenmuller: Mat. Res. Bull., 15, 1797-1804 (1980) [Non-Patent Document 5] S. Okada, Y. Takahashi, T. Kiyabu, T. Doi, J. Yamaki, T. Nishida: ECS Meeting Abstr., 602, 201 (2006) [Non-Patent Document 6] N. Yabuuchi, M. Kajiyama, J. Iwatate, H. Nishikawa, S. Hitomi, R. Okuyama, R. Usui, Y. Yamada, S. Komaba: Nat. Mater., 11, 512-517 (2012) [Non-Patent Document 7] H. Yamauchi, J. Ikejiri, F. Sato, H. Oshita, T. Honma, T. Komatsu: J. Am. Ceram. Soc., 102(11), 6658-6667(2019) Summary of the Invention [Problem to be solved by the invention]
[0022] As described above, in order to improve the performance of all-solid-state sodium storage batteries, it is important to have a technology that enhances the ionic conductivity between the solid electrolyte and the solid particles of the active material while ensuring the electronic conductivity of the electrodes.
[0023] The present inventors have focused on a technology in which an electrode composite precursor (electrode active material layer precursor) consisting of an active material precursor powder and a solid electrolyte powder is press-molded or further a solvent is added to form a slurry (paste), and then the slurry is fired to integrate the active material and the solid electrolyte, as described in Patent Document 11, Patent Document 12, and Non-Patent Document 7.
[0024] To improve the performance of a battery, it is necessary to increase the amount of electrode active material supported by increasing the amount of electrode mixture formed per unit area of the solid electrolyte layer surface in order to increase the capacity of the positive electrode formed per unit area of the solid electrolyte layer surface. However, as described in Patent Documents 11 and 12, the present inventors discovered a problem that when a mixture of an active material precursor and a solid electrolyte is thickly applied to the electrolyte surface and fired to increase the amount supported, only the electrode mixture layer sinters and shrinks, causing it to peel off from the electrolyte and fail to function as a battery.
[0025] As described above, the present inventors initially conducted intensive research into improving the performance of all-solid-state sodium storage batteries by directly forming an electrode mixture on the surface of an inorganic solid electrolyte, but when electrodes are formed directly on the surface of an inorganic solid electrolyte and integrated, the battery resistance is currently high and there is a limit to increasing the capacity per unit area. Therefore, the present inventors conducted extensive research into forming a battery using the electrode mixture and the inorganic solid electrolyte as separate components, rather than directly forming an electrode mixture on the surface of the inorganic solid electrolyte, and have now completed the present invention. The present invention can solve the problems (problems) of the conventional technology described above as well as problems newly discovered by the present inventors. [Means for solving the problem]
[0026] The above-mentioned problems (objectives) of the present invention are achieved by the following claims 1 to 29.
[0027] The first aspect of the present invention relates to a battery in which an organic solid electrolyte is interposed between an electrode mixture and an inorganic solid electrolyte. the organic solid electrolyte contains polyethylene glycol or polyethylene oxide, and further contains a sodium salt, and the weight of the organic solid electrolyte is in the range of 0.1 to 1.5. This relates to all-solid-state sodium storage batteries.
[0028] Claim 2 of the present invention is as follows: The organic solid electrolyte is interposed between the electrode mixture and the inorganic solid electrolyte, The organic solid electrolyte contains polyethylene glycol or polyethylene oxide. The organic solid electrolyte further contains a sodium salt and does not contain an organic solvent. This relates to all-solid-state sodium storage batteries.
[0030] Claims of the invention 3 The thickness of the organic solid electrolyte is within a range of 0.1 μm to 500 μm. OR 2Relates to an all-solid-state sodium battery described in
[0031] The claims of the present invention 4 relate to the all-solid-state sodium battery according to any one of claims 1 to 3 wherein the inorganic solid electrolyte is a sulfide-based, oxide-based, or hydride-based solid electrolyte having a thickness of 1 mm or less and a porosity of 20% or less.
[0032] The claims of the present invention 5 relate to the all-solid-state sodium battery according to any one of claims 1 to 4 wherein the inorganic solid electrolyte is aluminum oxide containing sodium.
[0033] The claims of the present invention 6 relate to the all-solid-state sodium battery according to any one of claims 1 to 5 wherein the inorganic solid electrolyte has a density in the range of 2.7 g / cc to 3.5 g / cc.
[0034] The claims of the present invention 7 relate to the all-solid-state sodium battery according to any one of claims 1 to a M b P c O d wherein the electrode binder contains a polyphosphoric acid transition metal oxide, and the polyphosphoric acid transition metal oxide is a crystal represented by the general formula Na 6 wherein M is at least one selected from Fe, Mn, Co, Ni, and V, and a, b, and c satisfy 0.0 < a ≤ 3.5, b = 1, 1.0 ≤ c ≤ 3.0, and 3.0 ≤ d ≤ 30.
[0035] The claims of the present invention 8 relate to the all-solid-state sodium battery according to any one of claims 1 to 7 wherein the electrode binder forms an active material cluster in which a plurality of individual particles in the range of 0.1 μm to 100 μm in particle size are connected.
[0036] The claims of the present invention 9The electrode mixture according to any one of claims 1 to 5, further comprising, in addition to the active material, at least one ion-conducting assistant selected from ethylene carbonate, polyethylene carbonate, polyethylene glycol, and polyethylene oxide. 8 The present invention relates to an all-solid-state sodium storage battery according to any one of the above items.
[0037] Claims of the invention 10 The electrode mixture contains at least one conductive assistant selected from the group consisting of metals, carbon materials, conductive polymers, and conductive glasses. Any of 1 to 9 The present invention relates to an all-solid-state sodium storage battery as described in the above.
[0038] Claims of the invention 11 The conductive assistant is at least one selected from the group consisting of powdered carbon, fibrous carbon, and flake carbon. to 10 The present invention relates to an all-solid-state sodium storage battery.
[0039] Claims of the invention 12 The electrode mixture according to any one of claims 1 to 5 has a porosity in the range of 5% to 50% when the organic solid electrolyte is excluded. 11 The present invention relates to an all-solid-state sodium storage battery according to any one of the above items.
[0040] Claims of the invention 13 The electrode mixture is porous with a pore size of 0.1 μm to 100 μm when the organic solid electrolyte is excluded. 12 The present invention relates to an all-solid-state sodium storage battery according to any one of the above items.
[0041] Claims of the invention 14 The electrode mixture contains an inorganic solid electrolyte powder having a particle size of 0.1 μm to 100 μm. 13 The present invention relates to an all-solid-state sodium storage battery according to any one of the above items.
[0042] Claims of the invention 15 The electrode mixture according to any one of claims 1 to 5 does not contain a resin-based binder. 14 The present invention relates to an all-solid-state sodium storage battery according to any one of the above items.
[0043] Claims of the invention 16 The all-solid-state sodium storage battery according to any one of claims 1 to 5 uses sodium metal, a sodium alloy or a sodium ion occluding material for the counter electrode. 15 The present invention relates to an all-solid-state sodium storage battery according to any one of the above items.
[0044] Claims of the invention 17 The present invention relates to an all-solid-state sodium storage battery having a structure in which the electrode mixture is in electrical contact with a current collector having electronic conductivity, and the current collector is made of a metal having through holes or a metal having no through holes, 16 The present invention relates to an all-solid-state sodium storage battery according to any one of the above items.
[0045] Claims of the invention 18 Claims 1 to 17 The present invention relates to a battery pack comprising the all-solid-state sodium storage battery according to the above.
[0046] Claims of the invention 19 Claims 1 to 17 The present invention relates to an electric device comprising the all-solid-state sodium storage battery according to claim 1. Effect of the Invention
[0047] According to the all-solid-state sodium storage battery of claim 1 of the present invention, since the organic solid electrolyte is interposed between the electrode mixture and the inorganic solid electrolyte, it is possible to realize a storage battery that exhibits excellent charge-discharge cycle characteristics and can be shut down by overcharging. In addition, since the organic solid electrolyte contains polyethylene glycol or polyethylene oxide, it can function as a solid electrolyte and as an adhesive that bonds the electrode mixture and the inorganic solid electrolyte. The organic solid electrolyte further contains a sodium salt, and when the weight of the organic solid electrolyte is taken as 1, the content of the sodium salt is within a range of 0.1 to 1.5. Therefore, the adhesive action between the electrode and the solid electrolyte can maintain ionic conductivity, and the charge / discharge cycle characteristics of the battery can be obtained.
[0048] According to claim 2 of the present invention, Since the organic solid electrolyte is interposed between the electrode mixture and the inorganic solid electrolyte, a storage battery can be realized that exhibits excellent charge / discharge cycle characteristics and can be shut down in the event of overcharging. Since the organic solid electrolyte contains polyethylene glycol or polyethylene oxide, it can function as a solid electrolyte and as an adhesive that bonds the electrode mixture and the inorganic solid electrolyte. In addition, since the organic solid electrolyte does not contain an organic solvent, expansion of the battery due to volatilization of the organic solvent can be suppressed.
[0050] Claims of the invention 3According to the invention, since the thickness of the organic solid electrolyte is in the range of 0.1 μm to 500 μm, it has excellent ionic conductivity and the energy density of the battery is increased.
[0051] The claims of the present invention 4 According to the invention, since the inorganic solid electrolyte is a sulfide-based, oxide-based, or hydride-based solid electrolyte with a thickness of 1 mm or less and a porosity of 20% or less, the energy density of the battery is increased and the ionic conductivity is maintained.
[0052] The claims of the present invention 5 According to the invention, since the inorganic solid electrolyte is aluminum oxide containing sodium, excellent electrical insulation and excellent heat resistance can be obtained.
[0053] The claims of the present invention 6 According to the invention, since the inorganic solid electrolyte has a density in the range of 2.7 g / cc to 3.5 g / cc, it has good ionic conductivity and is less likely to cause a micro short circuit during charging.
[0054] The claims of the present invention 7 According to the invention, the electrode composite material contains a polyphosphoric acid transition metal oxide, and the polyphosphoric acid transition metal oxide is a crystal represented by the general formula Na a M b P c O d where M is at least one selected from Fe, Mn, Co, Ni, and V, and a, b, and c satisfy 0.0 < a ≤ 3.5, b = 1, 1.0 ≤ c ≤ 3.0, and 3.0 ≤ d ≤ 30. Since the polyphosphoric acid transition metal oxide functions as an active material, the ionic conductivity, charge-discharge capacity, and output characteristics can be increased.
[0055] The claims of the present invention 8 According to the invention, since the electrode composite material forms an active material cluster in which a plurality of individual particles in the range of 0.1 μm to 100 μm in particle size are connected, a practical energy density can be obtained.
[0056] The claims of the present invention 9According to the present invention, since the electrode mixture contains, in addition to the active material, at least one ion conduction assistant selected from ethylene carbonate, polyethylene carbonate, polyethylene glycol, and polyethylene oxide, the ionic resistance of the electrode mixture can be reduced.
[0057] Claims of the invention 10 According to the present invention, since the electrode mixture contains at least one conductive assistant selected from metals, carbon materials, conductive polymers, and conductive glasses, high electronic conductivity can be obtained.
[0058] Claims of the invention 11 According to the present invention, since the conductive assistant is at least one selected from powdered carbon, fibrous carbon, and flake carbon, high electronic conductivity can be obtained.
[0059] Claims of the invention 12 According to the above, the electrode mixture, excluding the organic solid electrolyte, is porous with a porosity in the range of 5% to 50%, and therefore excellent electrical conductivity can be obtained.
[0060] Claims of the invention 13 According to the above, the electrode mixture, excluding the organic solid electrolyte, is porous with a pore size of 0.1 μm to 100 μm, and therefore excellent electrical conductivity can be obtained.
[0061] Claims of the invention 14 According to the above, since the electrode mixture contains inorganic solid electrolyte powder having a particle size of 0.1 μm to 100 μm, excellent electrical conductivity is obtained.
[0062] Claims of the invention 15 According to the present invention, since the electrode mixture does not contain a resin-based binder, the ion conductivity is increased and no adverse effects are exerted on the electrodes.
[0063] Claims of the invention 16 According to the report, the all-solid-state sodium storage battery uses sodium metal, a sodium alloy, or a sodium ion storage material for the counter electrode, and therefore a high-voltage, high-capacity battery can be obtained.
[0064] Claims of the invention 17 According to the document, an all-solid-state sodium storage battery has a structure in which the electrode mixture is in electrical contact with a current collector having electronic conductivity, and the current collector is made of a metal having through holes or a metal having no through holes, so that current can be collected from a power source, thereby improving the output characteristics (rapid charge / discharge characteristics).
[0065] Claims of the invention 18 According to the battery pack of the present invention, claims 1 to 17 Since the battery is made of the all-solid-state sodium storage battery according to any one of the above items, a high voltage can be obtained.
[0066] Claims of the invention 19 According to claims 1 to 17 By including the all-solid-state sodium storage battery according to any one of the above items, a versatile, small-sized, high-capacity electrical device can be realized. [Brief description of the drawings]
[0067] [Figure 1] FIG. 1 is a conceptual cross-sectional view of an all-solid-state sodium storage battery according to the present invention. [Diagram 2] FIG. 1 is a conceptual cross-sectional view of an all-solid-state sodium storage battery having a bipolar structure according to the present invention. [Diagram 3] FIG. 1 is a diagram comparing the charging curves of Example 3 and Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0068] An all-solid-state sodium storage battery according to one embodiment of the present invention will be described in detail below.
[0069] In order to achieve the above object, an all-solid-state sodium storage battery 1 according to the present invention is characterized in that it is an all-solid-state sodium storage battery configured by interposing an organic solid electrolyte 3 between an electrode mixture 2 (active material layer) and an inorganic solid electrolyte 4, as shown in Fig. 1. According to this configuration, the organic solid electrolyte 3 can move sodium ions via the electrode mixture 2 and the inorganic solid electrolyte 4 by applying a voltage.
[0070] In the all-solid-state sodium storage battery according to the present invention, the organic solid electrolyte is preferably a polyether polymerized with ethylene glycol or a derivative thereof, specifically, polyethylene glycol (PEG) or polyethylene oxide (PEO). The PEG or PEO functions as an adhesive that bonds the electrode mixture and the inorganic solid electrolyte, in addition to functioning as a solid electrolyte.
[0071] The PEG or PEO may contain a sulfur compound functional group, a nitrogen compound functional group, a phosphorus compound functional group, an acrylate functional group, or the like.
[0072] From the viewpoint of high functionality as an adhesive for binding the electrode mixture and the inorganic solid electrolyte, the PEG or PEO is preferably a polyether polymerized with ethylene glycol having a weight average molecular weight (Mw) of 1000 to 1,000,000 or a derivative thereof. Although it is possible to use other substances as the organic solid electrolyte, such as ethylene carbonate (EC), PEG or PEO is preferred because of its excellent functionality as an adhesive.
[0073] In particular, when the adherend, that is, the electrode mixture or inorganic solid electrolyte, has an uneven surface or has voids, the organic solid electrolyte penetrates into the unevenness or voids of the adherend, increasing the contact area between the electrode mixture and the inorganic solid electrolyte, thereby reducing the ionic resistance of the battery, which is preferable.
[0074] It is preferable that the organic solid electrolyte is liquefied and applied to the electrode mixture and / or the inorganic solid electrolyte. The organic electrolyte may be a non-flammable ionic liquid. The organic solid electrolyte can be liquefied by dissolving the target material in an organic solvent. The organic solvent is not particularly limited as long as it can dissolve the target material, and examples of the organic solvent include chain hydrocarbon solvents and cyclic hydrocarbon solvents. Examples of the chain hydrocarbon solvent include dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), tert-butyl isopropyl percarbonate, dichloromethane, nitriles, and alcohols, and examples of the cyclic hydrocarbon solvent include N-methyl-2-pyrrolidone (NMP), ethylene sulfite, vinyl ethylene carbonate (VEC), propylene carbonate (PC), 1,3-dioxane-2-one, benzene, and lactones.
[0075] The non-flammable ionic liquid is not particularly limited as long as it has ion conductivity, and examples of the non-flammable ionic liquid include pyridine-based, alicyclic amine-based, and aliphatic amine-based cations. By selecting the type of anion to be combined with the cation, a variety of non-flammable ionic liquids can be synthesized. Examples of the cation include imidazolium salts, pyridinium salts, phosphonium ions, and inorganic ions, and examples of the anion include bromide ions, triflates, tetraphenylborate, and hexafluorophosphate.
[0076] Non-flammable ionic liquids are, for example, cations such as imidazolinium and Br - , Cl - , BF4 - , PF6 - , (CF3SO2)2N - , CF3SO3 - , FeCl4 - Such a non-flammable ionic liquid can function as an electrolyte.
[0077] When assembling a battery, the battery can operate even if some of the organic solvent is present, but it is preferable to remove the organic solvent sufficiently by reducing pressure or heat treatment, since this can suppress the expansion of the battery due to the volatilization of the organic solvent. The removal method is not particularly limited, but for example, a drying method for electrode slurry used in lithium ion batteries can be adopted.
[0078] When the adherend, that is, the electrode mixture or inorganic solid electrolyte, is porous, the organic solid electrolyte flows into the electrodes through the pores on the adherend surface, thereby greatly reducing the resistance due to the ionic conduction of the battery (ionic resistance).
[0079] When the battery is overcharged, the PEG or PEO of the organic solid electrolyte is oxidatively decomposed, suppressing an increase in the battery voltage and eliminating its function as an adhesive, thereby providing a shutdown function that separates the electrode mixture from the inorganic solid electrolyte and increases the impedance of the battery.
[0080] From the viewpoint of strongly bonding the electrode mixture and the solid electrolyte, the higher the molecular weight of the PEG or PEO, the better, but if the weight-average molecular weight exceeds 1 million, the viscosity becomes too high, making handling difficult, and when a sodium salt, which will be described later, is added, the ion conductivity becomes low. Conversely, if the weight-average molecular weight is less than 1000, the adhesiveness is poor, and when the battery is subjected to vibration or impact, the interface between the electrode mixture and the inorganic solid electrolyte is destroyed, which is likely to be a factor in increasing the impedance of the battery.
[0081] At low molecular weights, the polymer exhibits hygroscopicity and the drying process takes a long time. Therefore, the weight average molecular weight is preferably 1,000 or more, more preferably 2,500 or more, with the upper limit being 1,000,000. These may be crosslinked or non-crosslinked.
[0082] The weight average molecular weight can be determined, for example, by measurement using liquid chromatography and a gel permeation chromatography (GPC) method.
[0083] From the viewpoint of increasing ion conductivity, it is preferable that the organic solid electrolyte further contains a sodium salt.
[0084] The sodium salt content is preferably 0.1 or more, more preferably 0.3 or more, and even more preferably 0.4 or more, assuming that the weight of the organic solid electrolyte is 1. However, if the content of the sodium salt is too high, the viscosity of the organic solid electrolyte increases and the adhesive action between the electrode mixture and the solid electrolyte decreases, so that the content is preferably 1.5 or less, more preferably 1.2 or less, and even more preferably 0.7 or less. An organic solid electrolyte with low adhesive action deteriorates the charge / discharge cycle characteristics of the battery.
[0085] The sodium salt may be at least one selected from the group consisting of sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), sodium tetrafluoroborate (NaBF4), sodium trifluoromethanesulfonate (NaCF3SO4), sodium bisoxalatoborate (NaBC4O8), sodium difluorophosphate (F2NaO2P), sodium bis-fluorosulfonylimide (F2NaNO4S2), sodium difluoroborate (NaBF2O), and the like. Of the above sodium salts, NaPF6 is preferred because it has a particularly high electronegativity and is easily ionized. An organic solid electrolyte containing NaPF6 has excellent input / output characteristics and charge / discharge cycle characteristics.
[0086] From the viewpoint of excellent ion conductivity and high energy density of the battery, the organic solid electrolyte has a thickness preferably in the range of 0.1 μm to 500 μm, more preferably in the range of 0.2 μm to 100 μm, further preferably in the range of 0.5 μm to 50 μm, and desirably in the range of 1 μm to 20 μm. Alternatively, the organic solid electrolyte has a mass per unit area of 0.1 mg / cm. 2 ~800mg / cm 2 It is preferable that the range is 0.2 mg / cm 2 ~500mg / cm 2 More preferably, the range is 0.5 mg / cm 2 ~100mg / cm 2 More preferably, 1 mg / cm 2 ~20mg / cm 2 is most preferred.
[0087] The inorganic solid electrolyte may be a sulfide-based, oxide-based, or hydride-based electrolyte, and one type may be used alone or two or more types may be used in combination. From the viewpoint of increasing the energy density of the battery and increasing the ion conductivity, it is preferable that such an inorganic solid electrolyte has a thickness of 1 mm or less and a porosity of 20% or less.
[0088] Sulfide systems include, for example, A4SiS4, A4GeS4, A3PS4, A 9.54 S 1.74 P 1.44 S 11.7 C l0.3 , A 10 GeP2S 12 , A 3.25 Ge 0.25 P 0.75 S4, A6PS5Cl, A2S-B2S3·AI, A2S-P2S5-ABH4, A2S-SiS2·A4SiO4, A2S-P2S5, A7P3S 11 , A 3.25 P 0.95 S4 (where A is Na or another alkali metal element containing Na).
[0089] The oxide system includes, for example, A 1.3 Al 0.3Ti 1.7 (PO4)3, A 0.34 La 0.51 TiO 2.94 , A7LaZr2O 12 , A4SiO4·A2BO3, A3PO4 - A4SiO4, A3BO3 - A2SiO4, A3BO3 - A2SO4, A 2.9 PO 3.3 N 0.46 , A 1.07 Al 0.69 Ti 1.46 (PO4)3, A 3.3 PO 3.8 N 0.22 , A 2.9 PO 3.3 N 0.46 (A represents Na or other alkali metal elements containing Na), aluminum oxide containing sodium, NASICON crystal (Na 1+x Zr2Si x P 3-x O 12 , 0 < x < 3), etc. can be mentioned.
[0090] Examples of the hydride - based ones include ABH4, ABH4 - AI, ABH4 - ABr, ABH4 - AF, ABH4 - ACl, etc. (A represents an alkali metal element).
[0091] Preferably, the above - mentioned inorganic solid electrolyte is within the range of 0% to 20% porosity. That is, an inorganic solid electrolyte that is as dense as possible is acceptable. By making the porosity 20% or less, the ionic conductivity can be increased. Conversely, if the porosity exceeds 20%, the ionic conductivity is poor and micro - short - circuits are likely to occur during charging.
[0092] In other words, preferably, the above - mentioned inorganic solid electrolyte is within the range of 2.7 g / cc to 3.5 g / cc in density. If it is less than 2.7 g / cc, there are too many voids, resulting in poor ionic conductivity and a high likelihood of micro - short - circuits occurring during charging.
[0093] However, the production of an inorganic solid electrolyte with a porosity of 0% is not practical unless a single crystal is used. For this reason, it is preferable to infiltrate an organic solid electrolyte into the voids of the inorganic solid electrolyte to further improve the ion conductivity. Here, if the density of the inorganic solid electrolyte exceeds 3.5 g / cc, it becomes difficult for the organic solid electrolyte to infiltrate, so it is preferable that the density is 3.5 g / cc or less.
[0094] The above density is the density when a container of a certain volume is filled with the inorganic solid electrolyte and the internal volume is taken as the volume, and more accurately means the aerated bulk density.
[0095] The shape is not particularly limited, but may be any of a film, sheet, pellet, and ribbon shape.
[0096] The inorganic solid electrolyte is preferably an oxide-based electrolyte, since it is less likely to generate toxic gases when it comes into contact with water. Among them, aluminum oxide containing sodium is preferable, since it has excellent electrical insulation properties and heat resistance.
[0097] Sodium-containing aluminum oxide is a crystal or ceramic expressed by the general formula Na2O-xAl2O3 (x=2~20), with a structure in which sodium ions are distributed between the two-dimensional layers formed by alumina blocks. Depending on how the alumina blocks are stacked, β-alumina (Na2O-11Al2O3) and β"-alumina (β-double prime alumina (Na2O-5Al2O3)) are known, but in either case, sodium ions move between the two-dimensional layers formed by the alumina blocks, so it functions as a solid electrolyte. Sodium-containing aluminum oxide can be synthesized, for example, by firing a mixture of α-alumina (Al2O3) and sodium carbonate at 1100℃~1500℃.
[0098] Aluminum oxide containing sodium preferably further contains at least one metal or oxide selected from Mg, Li, K, Rb, Zr, Pb, Y, Ag, Tl, Sr, Ca, and Fe. The content of these is preferably 5 vol.% or less with respect to the aluminum oxide containing sodium. Thereby, it is easy to obtain dense aluminum oxide containing sodium, and the ionic conductivity can be further improved.
[0099] The above inorganic solid electrolyte may be included in the electrode binder as a powder having a particle size of 0.1 μm to 100 μm.
[0100] The electrode binder includes a positive electrode binder (positive electrode active material layer) and a negative electrode binder (negative electrode active material layer). In the present invention, it is preferable that any of the electrode binders contains a polyphosphate transition metal oxide. In particular, when the electrode binder is used as a positive electrode binder, the polyphosphate transition metal oxide functions as an active material.
[0101] The polyphosphate transition metal oxide is preferably a crystal represented by the general formula Na a M b P c O d
[0102] From the viewpoint of high ionic conductivity, charge-discharge capacity, or output characteristics of the polyphosphate transition metal oxide, 0.0 < a ≦ 3.5, b = 1, 1.0 ≦ c ≦ 3.0, 3.0 ≦ d ≦ 30, and M is preferably at least one element selected from Fe, Mn, Co, Ni, and V.
[0103] Specifically, Na2FeP2O7, Na3Fe2(PO4)3, NaFe3P3O 12 , Na2Fe3(PO4)3, Na4Fe3(PO4)2(P2O7), Na2MnP2O7, Na2CoP2O7, Na2NiP2O7, Na2Fe 0.5 Mn 0.5 Examples include P2O7, Na3V2(PO4)3, NaVOPO4, Na9V3(P2O7)3(PO4)2, etc., and one or more of these may be used.
[0104] Among the above polyphosphate transition metal oxides, glass or crystallized glass is easy to synthesize as a polyphosphate transition metal oxide precursor, and has the characteristics of softening and flowing and being easy to crystallize during the firing (heat treatment) process at 700 °C or lower. Therefore, 0.0 < a ≤ 3.0, b = 1, 1.1 ≤ c ≤ 2.9, 3.5 ≤ d ≤ 12 is more preferable, 0.7 ≤ a ≤ 2.4, b = 1, 1.2 ≤ c ≤ 2.8, 4.0 ≤ d ≤ 11 is even more preferable, and 1.7 ≤ a ≤ 2.3, b = 1, 1.4 ≤ c ≤ 2.7, 5.0 ≤ d ≤ 10 is most preferable.
[0105] In the polyphosphate transition metal oxide, Li or K may be substituted for a part of the Na sites of the above materials, or the materials in which F, Cl, S, or B is substituted for a part of the O sites (octahedral positions) or P sites (octahedral positions) may also be used.
[0106] In addition to the polyphosphate transition metal oxide, the electrode composite material may further contain active materials used in sodium ion batteries, sodium metal batteries, sodium air batteries, sodium-sulfur batteries, sodium-metal chloride batteries, all-solid sodium storage batteries, etc. That is, in addition to the polyphosphate transition metal oxide, it may contain known sodium metal, known sodium alloys or known sodium ion storage materials.
[0107] When the electrode mixture is used as a positive electrode mixture, it may contain other positive electrode active materials in addition to the polyphosphate transition metal oxide. The positive electrode active material may be a known material including a transition metal oxide, a sulfur-based material, a solid solution-based material, or the like. When the electrode mixture is used as a negative electrode mixture, it is preferable to contain other negative electrode active materials in addition to the polyphosphate transition metal oxide, since a practical energy density cannot be obtained only with the polyphosphate transition metal oxide. It is preferable that the negative electrode active material contains known materials including a transition metal oxide, a sulfur-based material, sodium metal, a material that alloys with sodium, or a material that can reversibly absorb and release sodium ions.
[0108] The above electrode active material (positive electrode active material or negative electrode active material) is not particularly limited in shape, but preferably has a structure in which individual particles of the active material having a particle size in the range of 0.1 μm to 100 μm are connected together by a crystalline transition metal oxide polyphosphate. That is, the electrode mixture preferably forms an active material cluster in which individual particles having a particle size in the range of 0.1 μm to 100 μm are connected together.
[0109] Here, the particle size refers to the median diameter (D50) which is the central value on a volume basis in a laser diffraction / scattering particle size distribution measurement method.
[0110] In the all-solid-state sodium storage battery according to the present invention, the electrode mixture preferably contains, in addition to the active material, at least one selected from ethylene carbonate (EC), polyethylene carbonate (PEC), polyethylene glycol (PEG), and polyethylene oxide (PEO).
[0111] It is preferable that the electrode mixture contains at least one conductive agent selected from EC, PEC, PEG, and PEO, since this can reduce the ionic resistance of the electrode mixture.
[0112] The conductive agents EC, PEC, PEG, and PEO contained in the electrode mixture may be modified to the extent that their structure and properties are not significantly changed (that is, they may be derivatives).
[0113] Although it depends on the mass of the electrode mixture, the amount of EC, PEC, PEG, and PEO contained in the electrode mixture is 0.1 mg / cm 2 ~500mg / cm 2 It is preferable that the range is 0.2 mg / cm 2 ~250mg / cm 2 More preferably, the range is 0.5 mg / cm 2 ~100mg / cm 2 is more preferred.
[0114] According to this configuration, a material selected from EC, PEC, PEG, and PEO contained in the electrode mixture functions as an electrolyte that improves the ionic conductivity in the electrode mixture. In addition, the organic solid electrolyte interposed between the electrode mixture and the inorganic solid electrolyte is fused and integrated with the electrode mixture, resulting in a battery with low impedance. As a result, even if a thick electrode mixture is formed, an all-solid-state sodium storage battery can be obtained that can maintain a high discharge capacity and exhibit excellent charge-discharge cycle characteristics in a room temperature environment.
[0115] In addition, when the battery is overcharged, the material contained in the electrode mixture, selected from EC, PEC, PEG, and PEO, is oxidized and decomposed, thereby suppressing the increase in battery voltage.
[0116] Among the materials selected from EC, PEC, PEG, and PEO contained in the electrode mixture, from the viewpoint of excellent heat resistance of the electrode mixture, high ionic conductivity, and easy fusion with the organic solid electrolyte interposed between the electrode mixture and the inorganic solid electrolyte, a polymer material having a molecular weight of 500 or more selected from PEC, PEG, and PEO is preferred, and more preferably PEG or PEO. However, if the polymer material has a molecular weight of more than 200,000, the viscosity becomes too high, making it difficult to include it in the electrode mixture in the manufacturing method described below, and the ionic conductivity of the electrode mixture decreases. These may be crosslinked or non-crosslinked.
[0117] In addition, the electrode mixture preferably contains a conductive assistant. The conductive assistant is not particularly limited as long as it has electronic conductivity, and examples thereof include metals, carbon materials, conductive polymers, conductive glass, etc., but carbon materials are preferred from the viewpoint of high electronic conductivity and small specific gravity. Specific examples thereof include acetylene black (AB), ketjen black (KB), furnace black (FB), thermal black, lamp black, channel black, roller black, disc black, carbon black (CB), glassy carbon, etc., and one or more of these may be used.
[0118] The above-mentioned electrode mixture can be produced by filling a powder containing at least a transition metal oxide polyphosphate into a powder molding die, applying pressure to mold a pellet (tablet), and firing the pellet (tablet) at a temperature of 400°C to 2000°C in an inert gas or reducing gas atmosphere.
[0119] However, a high pressure exceeding 100 MPa is required to pelletize the transition metal oxide polyphosphate powder, and therefore a large-scale pressure device is required. Therefore, the transition metal oxide polyphosphate is preferably coated with or supported by a resin binder. By coating or supporting the surface of the transition metal oxide polyphosphate with a resin binder, it becomes possible to pelletize the powder at a pressure of 100 MPa or less.
[0120] By using such powder and molding under pressure, the resin binders bond together at a pressure of 1 MPa to 100 MPa, and dense pellets can be obtained. If the pressure during molding is less than 1 MPa, the resin binders do not bond together easily. On the other hand, if the pressure exceeds 100 MPa, the equipment becomes large-scale.
[0121] The resulting pellets are then fired in an inert gas or reducing gas atmosphere to soften and flow the transition metal polyphosphate oxide, resulting in an integrated electrode mixture. At the same time, the resin binder is thermally decomposed. Therefore, the electrode mixture (the fired pellets) does not contain resin, and a porous electrode mixture with a porosity in the range of 5% to 50% is obtained.
[0122] In an electrode composite material including not only a polyphosphate transition metal oxide but also an active material used in a sodium ion battery, a sodium metal battery, a sodium air battery, a sodium-sulfur battery, a sodium-metal chloride battery, an all-solid-state sodium storage battery, etc., it is preferable to coat or support not only the polyphosphate transition metal oxide but also these active materials with or without a resin-based binder, even when a conductive assistant is added.
[0123] The firing conditions are not particularly limited as long as the firing can be performed in an inert gas or reducing gas atmosphere at a temperature within the range of 400°C to 2000°C for 5 minutes or more. From the viewpoint of softening and flowing the transition metal oxide polyphosphate and thermally decomposing the resin binder, it is preferable to raise the temperature at a rate of 0.1°C / min to 50°C / min, maintain the temperature at 400°C to 2000°C, and maintain the temperature for 5 minutes to 10 hours.
[0124] From the viewpoint of the input / output characteristics and energy density of the battery, the electrode mixture after firing is set to have a thickness within the range of 10 μm to 5000 μm and a total weight per unit area of 1 mg to 5000 mg / cm. 2 It is preferable that the range is within the range of 100 μm.
[0125] Polyphosphate transition metal oxide coated with a resin-based binder can be obtained by adding a solvent to a mixed powder consisting of polyphosphate transition metal oxide and a resin-based binder, mixing the powder, removing the solvent by evaporation, and pulverizing or classifying the mixture. Note that unless the solvent is water, it is best to carry out the work in a dry environment (dew point -40°C or lower).
[0126] As a method for preparing the above mixed powder or for mixing by adding a solvent, a known mixing method can be used, for example, a tumbling mill, a vibration mill, a planetary mill, a rocking mill, a horizontal mill, an attritor mill, a jet mill, a crusher, a homogenizer, a fluidizer, a paint shaker, a mixer, etc.
[0127] As a method for removing the solvent by volatilization and pulverizing or classifying the mixture, a known granulation method can be applied, for example, a fluidized bed granulation method, an agitation and pulverization granulation method, a rolling granulation method, a spray-drying method, an extrusion granulation method, a coating granulation method, etc. Among these, the spray-drying method and the fluidized bed granulation method are particularly preferred.
[0128] In the spray drying method, for example, a suspension in which a transition metal oxide polyphosphate and a resin-based binder are dispersed is sprayed from above into a greenhouse heated to 50 to 300°C at a rate of 1 to 30 mL / min and an air pressure of 0.01 to 5 MPa to produce aggregated particles, which are then dried to obtain a granulated product.
[0129] In the fluidized bed granulation method, for example, the powder raw materials are placed in a fluidized bed granulation device, and hot air heated to 50 to 300°C is blown in from below to fluidize and mix the powder raw materials (granulated material precursor). A liquid in which a resin-based binder has been dissolved or dispersed is sprayed from a nozzle above into this mixed powder raw materials. The resin-based binder is sprayed uniformly onto the powder surface at 1 to 30 mL / min and an air pressure of 0.01 to 5 MPa to create agglomerated particles, which are then dried to obtain a granulated material.
[0130] To include a material selected from EC, PEC, PEG, and PEO in the electrode composite, the active material and these materials may be mixed and pelletized, but in the case of producing transition metal oxide polyphosphate crystals by firing transition metal oxide polyphosphate polycrystalline glass or glass, if the material is fired in a state in which EC, PEC, PEG, or PEO is already included, it will be thermally decomposed, and it will be impossible to include EC, PEC, PEG, or PEO in the composite. For this reason, it is necessary to include materials such as EC, PEC, PEG, and PEO after firing the transition metal oxide polyphosphate polycrystalline glass or glass.
[0131] Therefore, EC, PEC, PEG, PEO, etc. can be liquefied and applied to the fired polyphosphate transition metal oxide, or the fired polyphosphate transition metal oxide can be immersed in liquefied EC, PEC, PEG, PEO, etc., to allow the electrode mixture to contain a material selected from EC, PEC, PEG, and PEO.
[0132] For liquefying EC, PEC, PEG, PEO, etc., the temperature of the target material may be increased, but it is preferable to add an organic solvent to liquefy the material. The organic solvent is not particularly limited as long as it can dissolve and liquefy the target material. Examples include chain hydrocarbon solvents (DMC, DEC, EMC, dichloromethane, alcohols, etc.) and cyclic hydrocarbon solvents (NMP, benzene, lactones, etc.). The organic solvent is preferably removed by reducing pressure or by heat treatment. For example, a drying method for electrode slurry used in lithium ion batteries can be adopted.
[0133] When the thickness of the electrode composite is large, it is preferable to immerse the fired transition metal oxide polyphosphate in liquefied EC, PEC, PEG, PEO, etc., since it is difficult to penetrate simply by applying liquefied EC, PEC, PEG, PEO, etc. In this state, by creating a further reduced pressure environment, it is possible to penetrate deep into the pores contained in the fired transition metal oxide polyphosphate. The reduced pressure environment can be a pressure (negative pressure) lower than atmospheric pressure, for example, a negative pressure environment with a gauge pressure of 0 MPa to -0.1 MPa can be created using a vacuum pump.
[0134] The electrode mixture is preferably porous with a porosity in the range of 5% to 50%, excluding the material selected from EC, PEC, PEG, and PEO contained in the electrode mixture. If the porosity is less than 5%, EC, PEC, PEG, and PEO cannot be sufficiently contained in the electrode mixture. If the porosity is more than 50%, it is possible to contain a large amount of EC, PEC, PEG, PEO, etc. in the electrode mixture, but the proportion of active material in the electrode mixture is reduced, resulting in a low energy density.
[0135] Here, the porosity is a value calculated from the apparent density of the object and the true density of the constituent materials using the following formula.
[0136] Porosity (%) = 100 - (apparent density of object / true density of constituent material) x 100
[0137] In addition, the electrode mixture is preferably porous having a plurality of pores with a pore size of 0.1 μm to 100 μm, excluding the material selected from EC, PEC, PEG, and PEO contained in the electrode mixture. If the pore size is outside this range, it becomes difficult to sufficiently include EC, PEC, PEG, PEO, etc. in the electrode mixture in the manufacturing method of the electrode mixture described later. That is, if the pore size is less than 0.1 μm, EC, PEC, PEG, PEO, etc. are difficult to penetrate into the electrode mixture, and conversely, if it exceeds 100 μm, the strength of the electrode mixture is low and it is easily broken.
[0138] The all-solid-state sodium storage battery according to the present invention can be produced, for example, by closely adhering the electrode mixture obtained as described above to one surface of an inorganic solid electrolyte via an organic solid electrolyte in a dry environment with a dew point of −40° C. or lower, and sealing the battery in a state in which a counter electrode is provided on the other surface of the inorganic solid electrolyte.
[0139] The counter electrode is not particularly limited, and when the electrode mixture is used as a positive electrode mixture, the counter electrode may be an electrode mixture containing a negative electrode active material, a known sodium metal negative electrode, a known sodium alloy negative electrode, or a known sodium ion occluding negative electrode. When the electrode mixture is used as a negative electrode mixture, the counter electrode may be a positive electrode mixture, a known sodium alloy positive electrode, or a known sodium ion occluding positive electrode.
[0140] In addition, the all-solid-state sodium storage battery is preferably configured such that the above-mentioned organic solid electrolyte is also interposed between the counter electrode and the inorganic solid electrolyte.
[0141] That is, it is preferable that the all-solid-state sodium battery according to the present invention does not contain a resin-based binder in the electrode mixture, since the inclusion of a resin-based binder in the electrode mixture causes an increase in electronic resistance and ionic resistance.
[0142] Resin-based binders are compounds whose main molecular structure is carbon. Examples of resin-based binders include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyimide (PI), polyamide, polyamide-imide, polyacrylic, styrene-butadiene rubber (SBR), ethylene-vinyl acetate copolymer (EVA), polypropylene carbonate (PPC), styrene-ethylene-butylene-styrene copolymer (SEBS), carboxymethyl cellulose (CMC), xanthan gum, polyvinyl alcohol (PVA), polyvinyl butyral (PVB), ethylene vinyl alcohol, polyethylene (PE), polypropylene (PP), polyacrylic acid, lithium polyacrylate, sodium polyacrylate, potassium polyacrylate, ammonium polyacrylate, methyl polyacrylate, polyacrylonitrile, polyacrylate ... Examples of materials that can be used include ethyl acrylate, polyamine acrylate, polyacrylic ester, epoxy resin, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), nylon, vinyl chloride, silicone rubber, nitrile rubber, cyanoacrylate, urea resin, melamine resin, phenolic resin, latex, polyurethane, silylated urethane, nitrocellulose, dextrin, polyvinylpyrrolidone, vinyl acetate, polystyrene, chloropropylene, resorcinol resin, polyaromatic, modified silicone, methacrylic resin, polybutene, butyl rubber, 2-propenoic acid, cyanoacrylic acid, methyl methacrylate, glycidyl methacrylate, acrylic oligomer, 2-hydroxyethyl acrylate, polyacetal, alginic acid, starch, sucrose, lacquer, glue, and casein.
[0143] Many of these resin-based binders are thermally decomposed and carbonized at temperatures above 150℃, but polypropylene carbonate (PPC) is a binder that changes to carbon dioxide gas by heat treatment at 200℃ or higher, even in an inert or reducing environment, and disappears without leaving any carbon behind, making it preferable because it has very little effect on electrodes. The carbon generated by the thermal decomposition of resin-based binders has low conductivity unless fired at high temperatures, and can have a detrimental effect on electrodes.
[0144] In addition, the all-solid-state sodium storage battery according to the present invention is preferably structured such that the electrode mixture is in electrical contact with a current collector having electronic conductivity. The current collector may be either a metal having through holes or a non-through metal, but by using a non-through metal, an all-solid-state battery with a bipolar structure as shown in FIG. 2 can be produced. The bipolar electrode may be produced by contacting a current collector 6 made of a non-through metal such as a metal foil or metal plate with the electrode mixture 2, or may be produced by forming the current collector 6 on the electrode mixture by a method such as electroplating or vapor phase growth. A bipolar all-solid-state battery can obtain a high voltage with one cell.
[0145] On the other hand, when a metal having through holes is used as a current collector, the electrode mixture can be filled into the current collector to collect current three-dimensionally from the electrode mixture. This improves the electronic conductivity of the electrode mixture, resulting in a battery with excellent output characteristics. In addition, when a mixture containing an active material precursor is sintered to produce an electrode mixture, the active material precursor undergoes large volumetric shrinkage, generating large stress. However, by filling the electrode mixture into a non-penetrating metal, the cohesive stress is alleviated, and the occurrence of cracks in the electrode mixture can be suppressed. In addition, when an active material that undergoes a large volume change due to charging and discharging is used, the electrode mixture is prevented from falling off the current collector, resulting in a long-life battery.
[0146] The material of such a current collector is not particularly limited as long as it has electronic conductivity and can conduct electricity to the active material contained in the electrode mixture. For example, metal, carbon, conductive ceramics, conductive glass, etc. can be mentioned. Specifically, conductive materials such as gold, aluminum, carbon, copper, molybdenum, titanium, chromium, nickel, tantalum, tungsten, platinum, etc., and metals containing two or more of these conductive materials (for example, stainless steel, Al-Fe alloy, etc.) can be used. Among them, from the viewpoint of obtaining a battery with low material cost and excellent output characteristics, a current collector in which aluminum or an aluminum alloy is coated with carbon is preferable. More specifically, a current collector having a carbon layer with a thickness of 0.1 μm to 3 μm on the surface of the metal is preferable.
[0147] As described above, the shape of the current collector can be roughly divided into metals having through holes and non-through metals. Examples of metals having through holes include foam metals, embossed bodies having through holes, expanded bodies, punched bodies, nonwoven fabrics, and woven fabrics, and the porosity is preferably 10% to 98%. However, if the porosity is less than 10%, there is not much difference between the current collector and non-through metals, and if it exceeds 98%, the strength of the current collector is low and the electrode is easily damaged. Examples of non-through metals include foils, plates, non-through embossed bodies, and the like.
[0148] In this way, the electrode is composed of an electrode mixture and a current collector. However, if the battery's exterior body (battery case) is electrically conductive and can itself function as a current collector, a current collector is not necessarily required.
[0149] Although the all-solid-state sodium storage battery has been described above, various additions, modifications, or deletions are possible within the scope of the present invention. For example, the electrolyte of the all-solid-state sodium storage battery of the present invention may further include an electrolytic solution, an ionic liquid, or a gel electrolyte. For example, the carrier ion of the battery may be changed from sodium ion to other alkali metal ion (lithium ion, potassium ion, etc.) to form an all-solid-state lithium ion storage battery or an all-solid-state potassium ion storage battery.
[0150] A battery pack according to one aspect of the present invention is characterized by including the all-solid-state sodium storage battery of the present invention. That is, the all-solid-state sodium storage batteries of the present invention may be electrically connected to each other directly or via a bus bar to form a battery group consisting of two or more unit cells.
[0151] An electrical device according to one aspect of the present invention is characterized by including the all-solid-state sodium storage battery or battery pack according to the present invention.
[0152] Examples of electrical equipment include irons, whisks, all-in-one computers, clothes dryers, medical equipment, intercoms, wearable devices, video equipment, air conditioners, air circulators, gardening machinery, motorcycles, ovens, music players, music recorders, hot air heaters, toys, car components, flashlights, loudspeakers, car navigation systems, cassette stoves, home storage batteries, nursing care machinery, humidifiers, dryers, fuel dispensers, water dispensers, suction machines, safes, glue guns, mobile phones, portable information devices, air purifiers, air-conditioned clothing, game consoles, fluorescent lights, lint removers, cordless phones, coffee makers, -warmers, ice shaver, kotatsu, copy machines, haircutting equipment, shavers, lawn mowers, automobiles, lighting equipment, dehumidifiers, sealers, shredders, automated external defibrillators, rice cookers, stereos, stoves, speakers, trouser presses, smartphones, rice polishers, washing machines, toilet seats with cleaning functions, sensors, electric fans, submarines, blowers, vacuum cleaners, flying cars, tablets, body fat scales, fishing tackle, digital cameras, televisions, television receivers, video games, displays, disc changers, desktop computers, railways, televisions, electric carpets, desk lamps, electric stoves , electric pot, electric blanket, calculator, electric cart, electric wheelchair, power tool, electric car, electric float, electric toothbrush, telephone, electric bicycle, electric insect killer, induction cooker, electronic organizer, electronic musical instrument, electronic lock, electronic card, microwave oven, electronic mosquito repellent, electronic cigarette, telephone, power load leveler, toaster, hair dryer, walkie-talkie, clock, drone, food waste processor, laptop, incandescent light bulb, soldering iron, panel heater, halogen heater, fermentation machine, bread maker, hybrid car, personal computer, personal computer peripherals, hair clipper, panel heater, video camera, video Deo decks, airplanes, emergency lights, emergency batteries, ships, beauty equipment, printers, copiers, grinders, sprayers, facsimiles, forklifts, plug-in hybrid cars, projectors, hair dryers, hair irons, headphones, disaster prevention equipment, security equipment, home theaters, hot sandwich makers, hot plates, pumps, aroma diffusers, massage machines, mixers, mills, movie players, monitors, rice cake makers, water heaters, floor heating panels, radios, radio cassette players, lanterns, radio-controlled cars, laminators, remote controls, microwave ovens, water coolers, refrigerators, air coolers,Examples include air conditioners, cooling devices, robots, word processors, GPS, etc. EXAMPLES
[0153] <Example> Examples of the present invention will be described below in detail, but the present invention is not limited to these examples. In particular, in the examples, an all-solid-state sodium storage battery using β''-alumina as a solid electrolyte will be described as an example, but the present invention is not limited thereto. In addition, an active material contained in an electrode mixture will be described as Na2FeP2O7 as an example, but the present invention is not limited thereto.
[0154] <Preparation of Positive Electrode Active Material Precursor Powder> The positive electrode active material precursor was prepared by melt quenching. Sodium metaphosphate (NaPO3), iron oxide (Fe2O3), and orthophosphoric acid (H3PO4) were mixed as raw materials so that the composition was 40Na2O-20Fe2O3-40P2O5 in molar ratio, and melted at 1350°C for 1 hour in an air atmosphere. The obtained molten glass was poured out between a pair of cooling rollers and molded while being quenched to obtain a film-like glass body with a thickness of 0.1 to 1 mm. This glass body was ball milled using ZrO2 balls of φ20 mm for 10 hours, and passed through a resin sieve with an opening of 120 μm to obtain a glass coarse powder with an average particle size of 7 μm. Furthermore, this glass coarse powder was ball milled using ZrO2 balls of φ3 mm for 80 hours using ethanol as a grinding aid, to obtain a glass powder (positive electrode active material precursor powder) with an average particle size of 0.6 μm. Powder X-ray diffraction measurements confirmed that the glass powder was amorphous.
[0155] <Preparation of Positive Electrode Active Material Powder> The glass body obtained above was crystallized by firing at 650°C for 1 hour in a nitrogen atmosphere to obtain a crystal. This crystal was crushed in a ball mill using ZrO2 balls of φ20mm for 10 hours and passed through a resin sieve with a mesh size of 120μm to obtain a coarse powder with an average particle size of 7μm. Furthermore, this coarse powder was crushed in a ball mill using ZrO2 balls of φ3mm for 12 hours using ethanol as a grinding aid to obtain a crystal powder with an average particle size of 0.2μm. 70wt.% of this crystal powder was mixed with 30wt.% of polyethylene oxide nonylphenyl ether (mass average molecular weight: 660), which is a nonionic surfactant, as a carbon source, and then dried at 100°C for 1 hour. Then, it was fired at 620°C for 30 minutes in a nitrogen atmosphere to obtain a positive electrode active material powder with an average particle size of 0.2μm. As a result of powder X-ray diffraction measurement of this positive electrode active material powder, it was confirmed that the diffraction lines were derived from Na2FeP2O7 crystals.
[0156] <Preparation of electrode mixture (active material layer)> The electrode mixture (active material layer) was produced by filling a powder mold (made by NPA Systems Co., Ltd., Φ10mm) with a polypropylene carbonate (PPC)-coated mixture powder in an argon environment, applying a pressure of 30 MPa to form a pellet, which was then fired at 550°C for 1 h at 3°C / min in a nitrogen (N2) / hydrogen (H2) mixed gas (=96 / 4 vol.%) atmosphere, and then forming a 300 nm-thick gold film on one side of the pellet as a current collector using physical vapor deposition (PVD). During the firing process, all of the PPC contained in the electrode mixture was thermally decomposed and turned into carbon dioxide gas, so the weight of the resulting electrode mixture was minus the PPC.
[0157] The electrode mixture after firing had a thickness of 298 μm, a total weight of 0.0307 g, a diameter of 9.242 mm, and a weight of the active material contained in the electrode mixture of 0.02794 g. When the cross-section of the electrode mixture was examined using a scanning electron microscope (SEM), it was confirmed that the electrode mixture was composed of clusters in which multiple positive electrode active material particles were connected, and had a porous structure including pores. The clusters were formed when the positive electrode active material precursor powder was softened and flowed during firing of the composite powder, and the positive electrode active material powders were bonded together. It was confirmed that the positive electrode active material precursor powder was softened and flowed, and crystallized, precipitating Na2FeP2O7 crystals.
[0158] The composite powder coated with PPC was obtained by adding N-methyl-2-pyrrolidone (NMP) to the positive electrode active material precursor powder, positive electrode active material, conductive additive, and PPC (32.3:48.5:2.5:16.7 wt%) in a dry environment (dew point -40°C or less), mixing them in a planetary mixer (Thinky, Rentaro, 2000 rpm, 1 h), volatilizing and removing the NMP by heating and drying on a glass plate (80°C, 1 h), and pulverizing the mixture with a grinder (Nitto Scientific, AMM-140D) (1 h). The conductive additive used was a mixture of carbon black and vapor-grown carbon fiber (Showa Denko, VGCF-H) at a ratio of 5:1 wt.%.
[0159] <Inorganic solid electrolyte> Composition formula Na 1.6 Li 0.34 Al 10.66 O 17 Li2O stabilized β''-alumina (manufactured by Ionotec) was used as is. The thickness of the inorganic solid electrolyte was 1 mm.
[0160] <Preparation of organic solid electrolyte> The organic solid electrolyte was prepared by adding acetonitrile to polyethylene glycol (PEG) with a weight-average molecular weight (Mw) of 7000 and NaPF6 (1:0.3 wt.) and mixing them in a planetary mixer (Thinky Mixer, 2000 rpm, 1 h).
[0161] <Fabrication of all-solid-state sodium storage battery> (Example 1: All-solid-state sodium storage battery) The battery of Example 1 was manufactured in an argon environment by disposing the organic solid electrolyte prepared as described above between the electrode mixture and the inorganic solid electrolyte prepared as described above at a density of 0.005 g / cm. 2 The organic solid electrolyte was prepared by applying the organic solid electrolyte dissolved in acetonitrile to the electrode mixture with a brush and then drying the mixture in a vacuum (60°C, 1 h).
[0162] (Example 2: All-solid-state sodium storage battery) The battery of Example 2 was fabricated by using a mixture of PEG and NaPF6 (1:0.3 wt.) at 0.006 g / cm 2 The battery had the same structure as in Example 1. The mixture filled into the electrode mixture was prepared by immersing the electrode mixture in PEG and NaPF6 dissolved in acetonitrile, and then vacuum drying (60°C, 1 h) to remove the acetonitrile.
[0163] (Example 3: All-solid-state sodium storage battery) The battery of Example 3 had the same battery configuration as Example 2, except that a mixture of ethylene carbonate (EC) and NaPF6 (1:0.3 wt%) was filled into the electrode composite. The mixture to be filled into the electrode composite was prepared by immersing the electrode composite in EC and NaPF6 dissolved in diethyl carbonate (DEC), and then vacuum drying (60°C, 1 h) to remove the DEC.
[0164] (Comparative Example 1: All-solid-state sodium storage battery) The battery of Comparative Example 1 has the same battery configuration as that of Example 1, except that it does not include an organic solid electrolyte.
[0165] (Comparative Example 2: Flooded Sodium-Ion Battery) The battery of Comparative Example 2 does not have an organic solid electrolyte or an inorganic solid electrolyte, but instead uses a separator made of a laminate of a glass nonwoven fabric (GA-100, manufactured by Advantec) and a polyolefin microporous membrane (#2320, manufactured by Celgard) impregnated with 1M NaPF6 / (EC:DEC=1:1 vol.), and has the same battery configuration as Example 1.
[0166] <Battery testing> The battery test was carried out by repeating constant current charge and discharge under conditions of 60° C., 0.01 C rate, and cut-off voltage of 3.8 to 2.0 V. The results of the charge and discharge tests of Examples 1 to 3 and Comparative Examples 1 and 2 are shown below.
[0167] Example 1 In the all-solid-state sodium storage battery of Example 1, a mixture of PEG and NaPF6 was interposed between the electrode mixture and the inorganic solid electrolyte as an organic solid electrolyte, and thus the electrode mixture and the inorganic solid electrolyte were integrated. However, the resistance of the battery was high, and the discharge capacity of the active material was 10.1 mAh / g (0.42 mAh / cm 2 ) was.
[0168] Example 2 In the all-solid-state sodium storage battery of Example 2, a mixture of PEG and NaPF6 was interposed between the electrode mixture and the inorganic solid electrolyte as an organic solid electrolyte, thereby integrating the electrode mixture and the inorganic solid electrolyte. In addition, the electrode mixture was impregnated with the organic solid electrolyte. As a result, the discharge capacity of the active material was 89.2 mAh / g (3.72 mAh / cm 2 ) was.
[0169] Example 3 In the all-solid-state sodium storage battery of Example 3, a mixture of PEG and NaPF6 was interposed between the electrode mixture and the inorganic solid electrolyte as an organic solid electrolyte, thereby integrating the electrode mixture and the inorganic solid electrolyte. In addition, the electrode mixture was impregnated with the organic solid electrolyte. As a result, the discharge capacity of the active material was 92.6 mAh / g (3.86 mAh / cm 2 ) was.
[0170] Comparative Example 1 The all-solid-state sodium storage battery of Comparative Example 1 did not have an organic solid electrolyte, and therefore the electrode mixture and the inorganic solid electrolyte were not integrated. In addition, the discharge capacity of the active material was 0.0 mAh / g (0 mAh / cm 2 ), which did not function as a battery at all. This means that there was a large resistance to the flow of ions at the interface between the electrodes and the solid electrolyte, even at a very small current of 0.01 C rate.
[0171] Comparative Example 2 The discharge capacity of the active material of the flooded sodium ion battery of Comparative Example 2 was 94.2 mAh / g (3.92 mAh / cm 2 ) was.
[0172] Table 1 shows the battery test results for the above-mentioned Examples 1-3 and Comparative Examples 1-2.
[0173] [Table 1]
[0174] <Battery overcharge test> The battery overcharge test was performed by constant current charging at 60°C, 0.01C rate, and charge cutoff voltage of 4.5V. FIG. 3 shows a comparison of the charge curves of Example 3 and Comparative Example 2. The vertical axis shows the battery voltage, and the horizontal axis shows the charge time. Charging for more than 100 hours is in the overcharge region. As is clear from FIG. 3, a charge plateau was confirmed near 4.2V in the battery of Example 3, and the charge did not reach 4.5V, which is the charge cutoff voltage. On the other hand, a charge plateau was not confirmed near 4.2V in the battery of Comparative Example 2, and the battery was charged up to the charge cutoff voltage. It is believed that the organic solid electrolyte interposed between the electrode mixture and the inorganic solid electrolyte in the battery of Example 3 was oxidized and decomposed near 4.2V. This result shows that overcharging can be suppressed by providing an organic solid electrolyte in the battery (see Table 2).
[0175] [Table 2]
[0176] Furthermore, the battery of Example 3 was charged at a constant current and constant voltage until the SOC (State of Charge) reached 200% under conditions of 60°C, 0.01C rate, and charge cutoff voltage of 4.5V, and then discharged at a constant current of 0.1C rate until the SOC reached 2.0V. However, no discharge capacity was observed. It is believed that the organic solid electrolyte was oxidized and decomposed, which increased the battery resistance and caused the battery to shut down. [Industrial Applicability]
[0177] The all-solid-state sodium storage battery according to the present invention exhibits excellent charge-discharge cycle characteristics while maintaining a high discharge capacity in a room temperature environment, and can be shut down by overcharging. For this reason, it is expected to be applied to EVs (electric vehicles) and stationary power sources. [Explanation of symbols]
[0178] 1. Cross-sectional view of an all-solid-state sodium battery 2 electrode mixture 3 Organic solid electrolyte 4 Inorganic solid electrolyte 5. Opposite 6 Current collector 11 Cross-sectional concept of a bipolar battery
Claims
1. The organic solid electrolyte is interposed between the electrode mixture and the inorganic solid electrolyte, the organic solid electrolyte comprises polyethylene glycol or polyethylene oxide; The organic solid electrolyte further contains a sodium salt, and the weight of the organic solid electrolyte is in the range of 0.1 to 1.
5.
2. An organic solid electrolyte is interposed between an electrode mixture and an inorganic solid electrolyte, the organic solid electrolyte comprises polyethylene glycol or polyethylene oxide; The all-solid-state sodium storage battery, wherein the organic solid electrolyte further contains a sodium salt and does not contain an organic solvent.
3. The thickness of the organic solid electrolyte is in the range of 0.1 μm to 500 μm. The all-solid-state sodium storage battery according to claim 1 or 2.
4. The inorganic solid electrolyte is a sulfide-based, oxide-based, or hydride-based solid electrolyte having a thickness of 1 mm or less and a porosity of 20% or less. The all-solid-state sodium storage battery according to any one of claims 1 to 3.
5. The inorganic solid electrolyte is aluminum oxide containing sodium. The all-solid-state sodium storage battery according to any one of claims 1 to 4.
6. The inorganic solid electrolyte has a density in the range of 2.7 g / cc to 3.5 g / cc; The all-solid-state sodium storage battery according to any one of claims 1 to 5.
7. the electrode mixture comprises a transition metal oxide polyphosphate; The transition metal polyphosphate oxide has the general formula Na a M b P c O d wherein M is at least one selected from Fe, Mn, Co, Ni and V; and a, b and c are in the range of 0.0<a≦3.5, b=1, 1.0≦c≦3.0, 3.0≦d≦30.
8. The electrode mixture forms active material clusters in which a plurality of particles having a particle size in the range of 0.1 μm to 100 μm are connected together. The all-solid-state sodium storage battery according to any one of claims 1 to 7.
9. 9. The all-solid-state sodium storage battery according to claim 1, wherein the electrode mixture contains, in addition to the active material, at least one ion-conducting assistant selected from ethylene carbonate, polyethylene carbonate, polyethylene glycol, and polyethylene oxide.
10. 10. The all-solid-state sodium storage battery according to claim 1, wherein the electrode mixture contains at least one conductive assistant selected from the group consisting of metals, carbon materials, conductive polymers, and conductive glasses.
11. The all-solid-state sodium storage battery according to claim 10, wherein the conductive assistant is at least one selected from the group consisting of powdered carbon, fibrous carbon, and flake carbon.
12. The electrode mixture is porous, excluding the organic solid electrolyte, and has a porosity in the range of 5% to 50%. The all-solid-state sodium storage battery according to any one of claims 1 to 11.
13. The electrode mixture is porous with a pore size of 0.1 μm to 100 μm when the organic solid electrolyte is excluded. The all-solid-state sodium storage battery according to any one of claims 1 to 12.
14. The electrode mixture contains an inorganic solid electrolyte powder having a particle size of 0.1 μm to 100 μm. The all-solid-state sodium storage battery according to any one of claims 1 to 13.
15. The electrode mixture does not contain a resin-based binder. The all-solid-state sodium storage battery according to any one of claims 1 to 14.
16. The all-solid-state sodium storage battery uses sodium metal, sodium alloy or sodium ion storage material for the counter electrode. The all-solid-state sodium storage battery according to any one of claims 1 to 15.
17. An all-solid-state sodium storage battery having a structure in which the electrode mixture and a current collector having electronic conductivity are in electrical contact with each other, The current collector is made of a metal having through holes or a metal having no through holes. The all-solid-state sodium storage battery according to any one of claims 1 to 16.
18. A battery pack comprising the all-solid-state sodium storage battery according to any one of claims 1 to 17.
19. An electrical device comprising the all-solid-state sodium storage battery according to any one of claims 1 to 17.
Citation Information
Patent Citations
All-solid battery
JP2010015782A
Negative electrode material for sodium secondary battery, method for producing the same, negative electrode for sodium secondary battery, sodium secondary battery, and electrical equipment including the same
JP2013171798A
Positive electrode material for sodium secondary battery, method for producing the positive electrode material for sodium secondary battery, electrode for sodium secondary battery using the positive electrode material for sodium secondary battery, sodium secondary battery including the electrode for sodium secondary battery, and electrical device using the sodium secondary battery
JP2014229452A
All-solid type sodium ion secondary battery, and method for manufacturing the same
JP2015005466A
Negative electrode for sodium ion secondary battery, method for manufacturing the same, and sodium ion secondary battery
JP2015028922A